A Simple Synthesis of Triangular All‐Metal Aromatics Allowing Access to Isolobal All‐Metal Heteroaromatics. Issue 35 (6th July 2015) - Wang, Yanlan; Deyris, Pierre‐Alexandre; Caneque, Tatiana; Blanchard, Florent; Li, Yanling; Bigi, Franca; Maggi, Raimondo; Blanchard, Sebastien; Maestri, Giovanni; Malacria, Max
Abstract: A simple synthetic method allows the one‐pot assembly of C 3 ‐symmetric, 44‐core‐valence‐electron, triangular Pd or Pt clusters and their heterobimetallic mixed Pd/Pt analogues. These mixed metal complexes are the first examples of stable triangular all‐metal heteroaromatics. In contrast to traditional heteroaromatic molecules formed combining main‐group elements, they actually retain structural and electronic features of their homonuclear analogues. Abstract : Metals only please : A simple method delivers stable, triangular, C 3 ‐symmetric, 44 core valence electron, Pd3, Pt3 and heterobimetallic mixed Pd/Pt clusters. Showing the same high symmetry and delocalized bonding mode of their homonuclear peers, these mixed‐metal clusters are the first examples of stable trinuclear all‐metal heteroaromatics.